2022
DOI: 10.1126/scitranslmed.abo5228
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of proteolytic targeting of LCK as a therapeutic approach in T cell acute lymphoblastic leukemia

Abstract: T cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy, and there is an unmet need for targeted therapies, especially for patients with relapsed disease. We have recently identified pre–T cell receptor and lymphocyte-specific protein tyrosine kinase (LCK) signaling as a common therapeutic vulnerability in T-ALL. LCK inhibitor dasatinib showed efficacy against T-ALL in preclinical studies and in patients with T-ALL; however, this is transient in most cases. Leveraging the proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Error represents SD. c CRBN-DDB1 binding determined by fluorescent polarization assay. Error represents SEM ( n = 3). d Data previously reported in Hu et al …”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Error represents SD. c CRBN-DDB1 binding determined by fluorescent polarization assay. Error represents SEM ( n = 3). d Data previously reported in Hu et al …”
mentioning
confidence: 86%
“…However, IMiDs are well-known to be inherently unstable, readily undergoing hydrolysis even under relatively mild conditions, such as incubation in commonly utilized cell culture media . We recently reported that phenyl glutarimide (PG)-based PROTACs retained cereblon affinity while displaying improved chemical stability and, consequently, improved protein degradation efficacy and cellular potency. We also found PG-based PROTACs displaying improved selectivity profile with respect to the recruitment of classical off-target neosubstrates such as GSPT1. , However, while PG- PROTACs proved more stable than the corresponding IMiD-based PROTACs, they are still liable to hydrolyze in cell culture media. Moreover, the C-3 carbon of the glutarimide ring in PG was found to readily racemize in cell culture media, with up to 24% inversion over 24 h .…”
mentioning
confidence: 99%
See 3 more Smart Citations